High-flux low-pressure composite membrane and preparation method thereof

By adopting the preparation method of high-flux and low-pressure composite membranes in water treatment technology, and using polyamine monomers and polymers to perform interfacial polymerization with acid chloride oil phase systems, the problem of reduced desalination rate at low pressure in the existing technology is solved. It achieves high throughput and good retention performance, and is suitable for industrial production.

CN119345920APending Publication Date: 2025-01-24XIAMEN BAILIN WATER PURIFICATION TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311599191.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-11-28
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Among the existing water treatment technologies, ultramicrofiltration and reverse osmosis technology have reduced desalination rates under low pressure conditions, and reverse osmosis technology consumes high energy and has a large proportion of wastewater, which cannot effectively remove heavy metal ions and some viruses, and cannot retain beneficial to the human body. Trace elements.

Method used

A high-flux low-pressure composite membrane preparation method is adopted, by adding low-activity small-molecule polyamine monomers and high-activity cationic polyamine polymers into the aqueous phase system, and combining them with the acid chloride oil phase The system undergoes interfacial polymerization to prepare a high-flux composite membrane that can operate stably at low pressure.

Benefits of technology

The high -throughput and good interception performance under low pressure, reducing the operating pressure of the membrane, and by regulating the water phase system composition and process, the performance of the composite film can be effectively regulated, and it is suitable for large -scale industrialized production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004573542950000051
    Figure BDA0004573542950000051
  • Figure BDA0004573542950000101
    Figure BDA0004573542950000101
  • Figure BDA0004573542950000111
    Figure BDA0004573542950000111
Patent Text Reader

Abstract

The invention provides a high-flux low-pressure composite membrane and a preparation method thereof. The preparation method comprises the following steps: firstly, obtaining a porous ultrafiltration base membrane; then sequentially adding polyamine micromolecular monomers, cationic polyamine macromolecules and a surfactant into deionized water, and uniformly dispersing to obtain a water phase solution; dissolving an acyl chloride monomer in a second organic solvent to obtain an oil phase solution; and finally, dipping the porous ultrafiltration base membrane in a water phase solution, putting the porous ultrafiltration base membrane into an oil phase solution for interfacial polymerization, and carrying out heat treatment, soaking and rinsing to obtain the high-flux low-pressure composite membrane. According to the water-phase solution disclosed by the invention, the polymerization reaction degree is controllable and the process is uniform by utilizing polyamine micromolecules with relatively low activity, and cationic polyamine macromolecules with relatively high activity are added to participate in the reaction, so that the crosslinking degree of the macromolecules is improved, and the effects of maintaining the desalination rate and remarkably improving the flux of the composite membrane are achieved. In addition, the positive charge characteristic of the cationic high-molecular polymer is utilized, so that the removal effect of the composite membrane on cations can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of water treatment, and in particular to a high-flux low-pressure composite membrane and a preparation method thereof. Background Art

[0002] At present, household water purifiers on the market are mainly based on ultrafiltration, nanofiltration, and reverse osmosis technologies. Ultrafiltration technology mainly removes bacteria, viruses, colloids, silt, rust, etc., but cannot effectively remove harmful substances such as heavy metal ions, small molecular organic matter, and some viruses. Reverse osmosis technology can remove almost all substances other than water and produce ultrapure water, but it cannot retain trace elements that are beneficial to the human body. Moreover, due to its large osmotic pressure, it consumes a lot of energy to provide driving force, and its wastewater generation ratio is relatively high, so it has many limitations in daily use. Conventional reverse osmosis membranes have a greatly reduced desalination rate under low pressure conditions, and cannot operate stably relying solely on tap water pressure. Summary of the invention

[0003] The object of the present invention is to provide a high-flux low-pressure composite membrane, which can operate stably under low pressure and has high flux and good interception performance.

[0004] Another object of the present invention is to provide a method for preparing a high-throughput low-pressure composite membrane, which comprises a new aqueous phase system composed of low-activity small-molecule polyamine monomers, high-activity cationic polyamine polymers and surfactants, and an interfacial polymerization reaction with an acyl chloride oil phase system to prepare a high-throughput new composite membrane that can operate stably under low pressure. The method is simple, highly operable and applicable, and can effectively regulate the performance of the high-throughput low-pressure composite membrane according to the regulation of the aqueous phase system components and the control of the process, and is suitable for large-scale industrial production.

[0005] The present invention solves the technical problem by adopting the following technical solutions.

[0006] The present invention provides a method for preparing a high-flux low-pressure composite membrane, comprising the following steps:

[0007] S1, dissolving a polymer resin in a first organic solvent, adding a porogen and stirring and dissolving at 60-90° C., filtering, standing and degassing to obtain a polymer resin casting solution;

[0008] S2, the polymer resin casting solution is vacuum degassed and then coated on a non-woven fabric substrate, and then immersed in a coagulation bath at 30 to 70° C. for phase inversion to obtain a wet porous ultrafiltration base membrane;

[0009] S3, adding polyamine small molecule monomer, cationic polyamine polymer and surfactant in deionized water in sequence and dispersing them evenly to obtain an aqueous phase solution;

[0010] S4, dissolving the acyl chloride monomer in a second organic solvent to obtain an oil phase solution;

[0011] S5. After immersing the porous ultrafiltration base membrane in the aqueous solution, placing it in the oil solution for interfacial polymerization, and performing heat treatment, soaking and rinsing to obtain a high-flux low-pressure composite membrane.

[0012] The invention provides a high-flux low-pressure composite membrane, which is prepared according to the preparation method.

[0013] The high-flux low-pressure composite membrane and the preparation method thereof according to the embodiment of the present invention have the following beneficial effects:

[0014] The present invention provides a new water phase system, and makes it interfacially polymerized with an oil phase system to prepare a high-flux low-pressure composite membrane. The water phase solution system uses polyamine monomers with low reactivity among small molecules, so that the reaction rate of the interfacial polymerization reaction between the water phase solution and the oil phase solution can be reduced, and the degree of reaction can be controlled by changing the reaction conditions, thereby producing a relatively loose polymer layer. The water phase system also uses polyamine polymers with high reactivity and a large number of cationic groups among macromolecules. Some amino groups in the polyamine polymer react with acyl chloride groups in the oil phase monomer to increase the crosslinking degree, thereby providing a loose structure of the separation layer, and the unreacted amino groups can provide positive charges to increase the cation interception performance, thereby preparing a high-performance composite membrane with high flux and low pressure.

[0015] The preparation method of the present invention is simple, operable and highly applicable, and can effectively regulate the performance of the high-throughput low-pressure composite membrane by regulating the components of the aqueous solution system and controlling the process, and has good commercial application value. DETAILED DESCRIPTION

[0016] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0017] The high-flux low-pressure composite membrane and the preparation method thereof according to the embodiments of the present invention are described in detail below.

[0018] A method for preparing a high-flux low-pressure composite membrane provided by an embodiment of the present invention comprises the following steps:

[0019] S1. Dissolve the polymer resin in the first organic solvent, add the porogen and stir to dissolve at 60-90° C., and obtain the polymer resin casting solution after filtering and standing for degassing.

[0020] Further, in a preferred embodiment of the present invention, the polymer resin is selected from one or more of polysulfone, polyethersulfone, polyacrylonitrile, and polyvinylidene fluoride, the first organic solvent is selected from N,N-dimethylacetamide (DMAc) or N,N-dimethylformamide (DMF), and the porogen is selected from one or more of polyethylene glycol, propanol, isopropanol, glycerol, polyvinyl pyrrolidone, and polyethylene oxide. Among them, the molecular weight of polyethylene glycol is 400-8000, polyvinyl pyrrolidone includes one of K30, K60, K70, K80, and K90, and the molecular weight of polyethylene oxide is 40000-1200000.

[0021] Furthermore, in a preferred embodiment of the present invention, in the polymer resin casting solution, the mass percentage of the polymer resin is 16-20wt%, and the mass percentage of the porogen is 1-12wt%.

[0022] S2. The polymer resin casting solution is vacuum degassed and then coated on a non-woven fabric substrate, and then immersed in a coagulation bath at 30-70° C. for phase inversion to obtain a wet porous ultrafiltration base membrane.

[0023] S3. Add polyamine small molecule monomers, cationic polyamine polymers and surfactants into deionized water in sequence and disperse them evenly to obtain an aqueous phase solution.

[0024] The aqueous phase system of the present invention can make the interfacial polymerization reaction system form a more uniform interfacial polymerization layer, thereby maintaining a certain desalination rate and significantly improving the flux of the composite membrane, and effectively reducing the operating pressure of the membrane. The aqueous phase system is composed of low-activity small molecule polyamine monomers, high-activity cationic polyamine polymers, and surfactants. Through this new aqueous phase system and the acyl chloride oil phase system, the low-activity small molecule monomers can reduce the reaction rate during the reaction process, making the polymerization process more uniform, and the purpose of controlling the degree of reaction can be achieved by adjusting the influencing factors such as reaction time and temperature. The high-activity cationic polyamine polymer can be well cross-linked with the interfacial polymerization layer, making the amide layer generated by the polymerization reaction more loose, thereby increasing the water transport channel of the membrane, and preparing a high-flux new composite membrane that can run stably under low pressure. In addition, the positively charged characteristics of the cationic polyamine polymer provide a partial cation blocking effect, produce a certain desalination effect, and complement the negative electricity reduced by the loose amide layer, improve the cation removal capacity, and achieve the effect of maintaining the desalination rate of the composite membrane.

[0025] Further, in a preferred embodiment of the present invention, the polyamine small molecule monomer is selected from one or more of piperazine, 2,2-dimethylpiperazine, 2,5-dimethylpiperazine, p-phenylenediamine, o-phenylenediamine, and s-phenylenediamine, and the cationic polyamine polymer is selected from one or more of polyacrylamine and polyethyleneimine, wherein the molecular weight of the polyacrylamine is 10,000 to 100,000, the molecular weight of the polyethyleneimine is 5,000 to 60,000, and the surfactant is selected from one or more of camphorsulfonic acid, sodium camphorsulfonate, sodium phosphate, and disodium hydrogen phosphate. Preferably, the molecular weight of polyacrylamine is 5,000 to 80,000. The structural formula of polyacrylamine is:

[0026]

[0027] Polyacrylamine is a high molecular polymer containing a large number of amino groups, which has a high reactivity. Its amino groups can react with the acyl chloride groups in the oil phase solution and are well combined with the polyamide composite layer, while the unreacted amino groups will provide a certain cation removal effect. It should be noted that the cationic polyamine polymers of the present invention include but are not limited to the types listed above, and other cationic polyamine polymers or polyelectrolytes are also within the scope of protection of the present invention.

[0028] Furthermore, in a preferred embodiment of the present invention, in the aqueous phase solution, the mass percentage of the polyamine small molecule monomer is 0-5.0wt%, the mass percentage of the cationic polyamine polymer is 0.01-5.0wt%, and the mass percentage of the surfactant is 0.01-2.0wt%.

[0029] S4, dissolving the acyl chloride monomer in a second organic solvent to obtain an oil phase solution.

[0030] Further, in a preferred embodiment of the present invention, the acyl chloride monomer is selected from one or more of trimesoyl chloride, isophthaloyl chloride, terephthaloyl chloride, and phthaloyl chloride, and the second organic solvent is selected from one or more of n-hexane, cyclohexane, n-heptane, ISOPAR G, and ISOPAR L. The acyl chloride monomers of the present invention include but are not limited to the types listed above, and other monomers within the scope of the acyl chloride monomers are also within the protection scope of the present invention.

[0031] Furthermore, in a preferred embodiment of the present invention, in the oil phase solution, the mass percentage of the acyl chloride monomer is 0.01-5.0 wt %.

[0032] S5. After the porous ultrafiltration base membrane is immersed in the aqueous solution, it is placed in the oil phase solution for interfacial polymerization, and subjected to heat treatment, soaking and rinsing to obtain a high-flux low-pressure composite membrane. The average pore size of the porous ultrafiltration base membrane of the present invention is 0.03 to 0.1 μm. Preferably, the average pore size of the porous ultrafiltration base membrane is 0.03-0.06 μm. The present invention can also use a commercially available ultrafiltration membrane, which is an ultrafiltration membrane comprising any one of polysulfone, polyethersulfone, polyacrylonitrile, and polyvinylidene fluoride.

[0033] Furthermore, in a preferred embodiment of the present invention, the immersion time is 0.5 to 30 minutes, and the interfacial polymerization time is 0.5 to 20 minutes. Preferably, the immersion time is 1 to 20 minutes, and the interfacial polymerization time is 0.5 to 15 minutes.

[0034] Furthermore, in a preferred embodiment of the present invention, the heat treatment temperature is 40-80°C, and the heat treatment time is 0.5-30 minutes. The steps of heat treatment and soaking and rinsing are: take out the membrane after interfacial polymerization, put it into a 40-80°C oven for heat treatment for 0.5-30 minutes, and finally soak and rinse it in deionized water to obtain a high-flux low-pressure composite membrane. Preferably, the heat treatment temperature is 50-70°C, and the heat treatment time is 1-10 minutes.

[0035] The present invention also provides a high-flux low-pressure composite membrane, which is prepared according to the above-mentioned preparation method. The aqueous phase solution of the present invention utilizes low-activity polyamine small molecules to make the polymerization reaction degree controllable and the process uniform, and by adding high-activity cationic polyamine polymers to participate in the reaction, the polymer cross-linking degree is increased, so as to maintain the desalination rate and significantly improve the flux of the composite membrane. In addition, the positive charge characteristics of the cationic polymer can be utilized to enhance the removal effect of the composite membrane on cations.

[0036] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0037] Example 1

[0038] This embodiment provides a high-flux low-pressure composite membrane, which is prepared according to the following method:

[0039] (1) 16 wt% of polymer resin is added to N,N-dimethylacetamide (DMAc) to dissolve, and 5 wt% of porogen is added, and the mixture is stirred and dissolved at 60°C, filtered, and allowed to stand for degassing to obtain a uniform and stable polymer resin casting solution. The prepared polymer resin casting solution is then vacuum degassed and coated on a non-woven fabric substrate, which is then immersed in a 70°C coagulation bath for phase inversion to obtain a wet porous ultrafiltration base membrane.

[0040] (2) Preparation of an aqueous phase solution: 0.3 wt % of piperazine, 0.1 wt % of polyacrylamide with a molecular weight of 6500 and 0.1 wt % of sodium camphorsulfonate were added to deionized water in sequence and dispersed evenly to prepare an aqueous phase solution.

[0041] (3) Preparation of oil phase solution: 0.1 wt % of trimesoyl chloride was dissolved in an organic solvent, ISOPAR G, to prepare an oil phase solution.

[0042] (4) Cut the homemade ultrafiltration base membrane into a certain size and place it in a homemade dipping tool to dry excess water on the membrane surface, then pour the aqueous solution prepared in step (2) into the ultrafiltration base membrane for dipping for 2 minutes.

[0043] (5) The membrane treated in step (4) is then transferred to another tooling, and the oil phase solution prepared in step (3) is poured into it for interfacial polymerization. The dipping time is 2 minutes.

[0044] (6) The membrane sheet treated in step (5) is taken out, placed in an oven for heat treatment at 70° C. for 2 min, and finally placed in deionized water for soaking and rinsing to obtain a high-flux, low-pressure composite membrane.

[0045] Example 2

[0046] In this embodiment, a high-flux low-pressure composite membrane is provided, which is prepared according to the following method:

[0047] (1) 16 wt% of polymer resin is added to N,N-dimethylacetamide (DMAc) to dissolve, and 5 wt% of porogen is added, and the mixture is stirred and dissolved at 60°C, filtered, and allowed to stand for degassing to obtain a uniform and stable polymer resin casting solution. The prepared polymer resin casting solution is then vacuum degassed and coated on a non-woven fabric substrate, which is then immersed in a 70°C coagulation bath for phase inversion to obtain a wet porous ultrafiltration base membrane.

[0048] (2) Preparation of an aqueous phase solution: 0.1 wt % of piperazine, 0.3 wt % of polyacrylamide with a molecular weight of 6500 and 0.1 wt % of sodium camphorsulfonate were added to deionized water in sequence and dispersed evenly to prepare an aqueous phase solution.

[0049] (3) Preparation of oil phase solution: 0.1 wt % of trimesoyl chloride was dissolved in an organic solvent, ISOPAR G, to prepare an oil phase solution.

[0050] (4) Cut the homemade ultrafiltration base membrane into a certain size and place it in a homemade dipping tool to dry excess water on the membrane surface, then pour the aqueous solution prepared in step (2) into the ultrafiltration base membrane for dipping for 2 minutes.

[0051] (5) The membrane treated in step (4) is then transferred to another tooling, and the oil phase solution prepared in step (3) is poured into it for interfacial polymerization. The dipping time is 2 minutes.

[0052] (6) The membrane sheet treated in step (5) is taken out, placed in an oven for heat treatment at 70° C. for 2 min, and finally placed in deionized water for soaking and rinsing to obtain a high-flux, low-pressure composite membrane.

[0053] Example 3

[0054] In this embodiment, a high-flux low-pressure composite membrane is provided, which is prepared according to the following method:

[0055] (1) 16 wt% of polymer resin is added to N,N-dimethylacetamide (DMAc) to dissolve, and 5 wt% of porogen is added, and the mixture is stirred and dissolved at 60°C, filtered, and allowed to stand for degassing to obtain a uniform and stable polymer resin casting solution. The prepared polymer resin casting solution is then vacuum degassed and coated on a non-woven fabric substrate, which is then immersed in a 70°C coagulation bath for phase inversion to obtain a wet porous ultrafiltration base membrane.

[0056] (2) Preparation of an aqueous phase solution: 0.3 wt % of piperazine, 0.1 wt % of polyacrylamide with a molecular weight of 6500 and 0.1 wt % of sodium camphorsulfonate were added to deionized water in sequence and dispersed evenly to prepare an aqueous phase solution.

[0057] (3) Preparation of oil phase solution: 0.3 wt % of trimesoyl chloride was dissolved in an organic solvent, ISOPAR G, to prepare an oil phase solution.

[0058] (4) Cut the homemade ultrafiltration base membrane into a certain size and place it in a homemade dipping tool to dry excess water on the membrane surface, then pour the aqueous solution prepared in step (2) into the ultrafiltration base membrane for dipping for 2 minutes.

[0059] (5) The membrane treated in step (4) is then transferred to another tooling, and the oil phase solution prepared in step (3) is poured into it for interfacial polymerization. The dipping time is 2 minutes.

[0060] (6) The membrane sheet treated in step (5) is taken out, placed in an oven for heat treatment at 70° C. for 2 min, and finally placed in deionized water for soaking and rinsing to obtain a high-flux, low-pressure composite membrane.

[0061] Example 4

[0062] In this embodiment, a high-flux low-pressure composite membrane is provided, which is prepared according to the following method:

[0063] (1) 16 wt% of polymer resin is added to N,N-dimethylacetamide (DMAc) to dissolve, and 5 wt% of porogen is added, and the mixture is stirred and dissolved at 60°C, filtered, and allowed to stand for degassing to obtain a uniform and stable polymer resin casting solution. The prepared polymer resin casting solution is then vacuum degassed and coated on a non-woven fabric substrate, which is then immersed in a 70°C coagulation bath for phase inversion to obtain a wet porous ultrafiltration base membrane.

[0064] (2) Preparation of an aqueous phase solution: 0.3 wt % of piperazine, 0.1 wt % of polyacrylamide with a molecular weight of 6500 and 0.1 wt % of sodium camphorsulfonate were added to deionized water in sequence and dispersed evenly to prepare an aqueous phase solution.

[0065] (3) Preparation of oil phase solution: 0.1 wt % of trimesoyl chloride was dissolved in an organic solvent, ISOPAR G, to prepare an oil phase solution.

[0066] (4) Cut the homemade ultrafiltration base membrane into a certain size and place it in a homemade dipping tool to dry excess water on the membrane surface, then pour the aqueous solution prepared in step (2) into the ultrafiltration base membrane for dipping for 2 minutes.

[0067] (5) The membrane treated in step (4) is then transferred to another tooling, and the oil phase solution prepared in step (3) is poured into it for interfacial polymerization. The dipping time is 2 minutes.

[0068] (6) The membrane sheet treated in step (5) is taken out, placed in an oven for heat treatment at 70° C. for 10 min, and finally placed in deionized water for soaking and rinsing to obtain a high-flux, low-pressure composite membrane.

[0069] Comparative Example 1

[0070] This comparative example provides a composite nanofiltration membrane, which is prepared according to the following method:

[0071] (1) 16 wt% of polymer resin is added to N,N-dimethylacetamide (DMAc) to dissolve, and 5 wt% of porogen is added, and the mixture is stirred and dissolved at 60°C, filtered, and allowed to stand for degassing to obtain a uniform and stable polymer resin casting solution. The prepared polymer resin casting solution is then vacuum degassed and coated on a non-woven fabric substrate, which is then immersed in a 70°C coagulation bath for phase inversion to obtain a wet porous ultrafiltration base membrane.

[0072] (2) Preparation of aqueous solution: Add 0.2 wt % of m-phenylenediamine into deionized water to prepare an aqueous solution.

[0073] (3) Preparation of oil phase solution: 0.1 wt % of trimesoyl chloride was dissolved in an organic solvent, ISOPAR G, to prepare an oil phase solution.

[0074] (4) Cut the homemade ultrafiltration base membrane into a certain size and place it in a homemade dipping tool to dry excess water on the membrane surface, then pour the aqueous solution prepared in step (2) into the ultrafiltration base membrane for dipping for 2 minutes.

[0075] (5) The membrane treated in step (4) is then transferred to another tooling, and the oil phase solution prepared in step (3) is poured into it for interfacial polymerization. The dipping time is 2 minutes.

[0076] (6) Take out the membrane after the treatment in step (5), put it into an oven for heat treatment at 70°C for 2 minutes, and finally soak and rinse it in deionized water to obtain a composite nanofiltration membrane

[0077] Test Example 1

[0078] This test example uses a flat membrane cross-flow filtration performance evaluation device to test the flux and separation performance of the high-flux low-pressure composite membranes prepared in Examples 1 to 4 and the composite nanofiltration membrane prepared in Comparative Example 1. The test methods for flux and inorganic salt retention rate are as follows:

[0079] The operating pressure was set to 0.45 MPa, the pre-pressing time was 30 min, and then the pressure was adjusted to 0.2 MPa. After 30 min of stable operation, a certain volume of filtrate was taken and the sampling time was recorded. The membrane flux F (L·m -2 ·h -1 bar -1 ); the corresponding inorganic salt retention rate was calculated by formula (2). All data are the average of three parallel tests under the same conditions. The spiked solution for the flux test was deionized water, and the spiked solution for the inorganic salt retention rate test was 250 mg / L MgSO4, 250 mg / L CaCl2, and 250 mg / L NaCl solution.

[0080]

[0081] In formula (1), F is the water flux, in liters per square meter per hour per bar [L / (m 2 ·h·bar)]; V is the volume of permeate collected in time t, in liters (L); A is the effective membrane area, in square meters (m 2 ) ; t is the time taken to collect V volume of permeate, in hours (h).

[0082]

[0083] In formula (2), R is the interception rate, %; C p is the conductivity of the permeate, in μS / cm; C f It is the conductivity of the test liquid, in μS / cm.

[0084] The flux and inorganic salt rejection test data of the high-flux low-pressure composite membranes prepared in Examples 1 to 4 and the composite nanofiltration membrane prepared in Comparative Example 1 are shown in Table 1.

[0085] Table 1 Flux and inorganic salt retention test data

[0086]

[0087] It can be seen from Table 1 that under appropriate process conditions, the high-flux, low-pressure composite membrane prepared with a new water phase system in an appropriate proportion can achieve a significant increase in flux and maintain good retention performance.

[0088] The embodiments described above are part of the embodiments of the present invention, rather than all of the embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. A method for preparing a high-flux, low-pressure composite membrane, characterized in that: The following steps are involved: S1, dissolving a polymer resin in a first organic solvent, adding a porogen and stirring and dissolving at 60-90° C., filtering, standing and degassing to obtain a polymer resin casting solution; S2, the polymer resin casting solution is vacuum degassed and then coated on a non-woven fabric substrate, and then immersed in a coagulation bath at 30 to 70° C. for phase inversion to obtain a wet porous ultrafiltration base membrane; S3, adding polyamine small molecule monomer, cationic polyamine polymer and surfactant in deionized water in sequence and dispersing them evenly to obtain an aqueous phase solution; S4, dissolving the acyl chloride monomer in a second organic solvent to obtain an oil phase solution; S5. After immersing the porous ultrafiltration base membrane in the aqueous solution, placing it in the oil solution for interfacial polymerization, and performing heat treatment, soaking and rinsing to obtain a high-flux low-pressure composite membrane.

2. The preparation method according to claim 1, characterized in that: In step S1, the polymer resin is selected from one or more of polysulfone, polyethersulfone, polyacrylonitrile, and polyvinylidene fluoride, the first organic solvent is selected from N,N-dimethylacetamide or N,N-dimethylformamide, and the porogen is selected from one or more of polyethylene glycol, propanol, isopropanol, glycerol, polyvinyl pyrrolidone, and polyethylene oxide.

3. The preparation method according to claim 1, characterized in that: In the polymer resin casting solution, the mass percentage of the polymer resin is 16-20wt%, and the mass percentage of the porogen is 1-12wt%.

4. The preparation method according to claim 1, characterized in that: In step S3, the polyamine small molecule monomer is selected from one or more of piperazine, 2,2-dimethylpiperazine, 2,5-dimethylpiperazine, p-phenylenediamine, o-phenylenediamine, and isophenyltriamine; the cationic polyamine polymer is selected from one or more of polyacrylamine and polyethyleneimine, wherein the molecular weight of the polyacrylamine is 10,000 to 100,000, the molecular weight of the polyethyleneimine is 5,000 to 60,000, and the surfactant is selected from one or more of camphorsulfonic acid, sodium camphorsulfonate, sodium phosphate, and disodium hydrogen phosphate.

5. The preparation method according to claim 1, characterized in that: In step S3, in the aqueous phase solution, the mass percentage of the polyamine small molecule monomer is 0-5.0wt%, the mass percentage of the cationic polyamine polymer is 0.01-5.0wt%, and the mass percentage of the surfactant is 0.01-2.0wt%.

6. The preparation method according to claim 1, characterized in that: In step S4, the acyl chloride monomer is selected from one or more of trimesoyl chloride, isophthaloyl chloride, terephthaloyl chloride, and phthaloyl chloride, and the second organic solvent is selected from one or more of n-hexane, cyclohexane, n-heptane, ISOPAR G, and ISOPAR L.

7. The preparation method according to claim 1, characterized in that: In the oil phase solution, the mass percentage of the acyl chloride monomer is 0.01-5.0 wt %.

8. The preparation method according to claim 1, characterized in that: In step S5, the immersion time is 0.5 to 30 minutes, and the interfacial polymerization time is 0.5 to 20 minutes.

9. The manufacturing process according to claim 6, characterized in that: In step S5, the heat treatment temperature is 40-80° C., and the heat treatment time is 0.5-30 min.

10. A high flux, low pressure composite membrane, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 9.

Citation Information

Cited By

  • Composite nanofiltration membrane as well as preparation method and application thereof

    CN120550652A